The evolution of primary progressive apraxia of speech - Josephs, Keith A. (Brain, 2014)
Primary progressive apraxia of speech is a recently described neurodegenerative disorder in which patients present with an isolated apraxia of speech and show focal degeneration of superior premotor cortex. Little is known about how these individuals progress over time, making it difficult to provide prognostic estimates. Thirteen subjects with primary progressive apraxia of speech underwent two serial comprehensive clinical and neuroimaging evaluations 2.4 years apart [median age of onset = 67 years (range: 49–76), seven females]. All underwent detailed speech and language, neurological and neuropsychological assessments, and magnetic resonance imaging, diffusion tensor imaging and (18)F-fluorodeoxyglucose positron emission tomography at both baseline and follow-up. Rates of change of whole brain, ventricle, and midbrain volumes were calculated using the boundary-shift integral and atlas-based parcellation, and rates of regional grey matter atrophy were assessed using tensor-based morphometry. White matter tract degeneration was assessed on diffusion-tensor imaging at each time-point. Patterns of hypometabolism were assessed at the single subject-level. Neuroimaging findings were compared with a cohort of 20 age, gender, and scan-interval matched healthy controls. All subjects developed extrapyramidal signs. In eight subjects the apraxia of speech remained the predominant feature. In the other five there was a striking progression of symptoms that had evolved into a progressive supranuclear palsy-like syndrome; they showed a combination of severe parkinsonism, near mutism, dysphagia with choking, vertical supranuclear gaze palsy or slowing, balance difficulties with falls and urinary incontinence, and one was wheelchair bound. Rates of whole brain atrophy (1.5% per year; controls = 0.4% per year), ventricular expansion (8.0% per year; controls = 3.3% per year) and midbrain atrophy (1.5% per year; controls = 0.1% per year) were elevated (P ≤ 0.001) in all 13, compared to controls. Increased rates of brain atrophy over time were observed throughout the premotor cortex, as well as prefrontal cortex, motor cortex, basal ganglia and midbrain, while white matter tract degeneration spread into the splenium of the corpus callosum and motor cortex white matter. Hypometabolism progressed over time in almost all subjects. These findings demonstrate that some subjects with primary progressive apraxia of speech will rapidly evolve and develop a devastating progressive supranuclear palsy-like syndrome ∼ 5 years after onset, perhaps related to progressive involvement of neocortex, basal ganglia and midbrain. These findings help improve our understanding of primary progressive apraxia of speech and provide some important prognostic guidelines.